Refugee workers, 1941 (1941)
1941 1939-1945 "Refugee workers, 1941" [HFR0188], 1941 Following the fall of France, refugees from Europe began to arrive in large numbers. In May 1941, special employment exchanges were opened in London to register foreign nationals for employment and training. This extract from the London Trades Council delegate meeting of 12 June 1941 urges unions to recruit refugee workers and condemns a suggestion that they should wear badges or other distinguishing markers.